Implementasi Model Pembelajaran Doscovery Learning pada Pembelajaran Keterampilan Berbicara di SD Inpres Kompleks BTN IKIP - Rosdiah Salam; St. Nursiah B; Muh. Faisal (Seminar Nasional LP2M UNM, 2019)
Indonesian language skills are four interrelated skills namely listening skills, speaking skills, reading skills, and writing skills. Of the four skills, one of the most important language skills in daily life is speaking skills which are an effective oral communication medium. As Tarigan, (2008: 3) says